2012
DOI: 10.7555/jbr.26.20120003
|View full text |Cite
|
Sign up to set email alerts
|

X-ray irradiation selectively kills thymocytes of different stages and impairs the maturation of donor-derived CD4+CD8+ thymocytes in recipient thymus

Abstract: The aim of the present study was to determine whether the sensitivity of thymocytes to X-ray radiation depends on their proliferative states and whether radiation impairs the maturation of donor-derived thymocytes in recipient thymus. We assigned 8-week-old C57BL/6J mice into three treatment groups: 1) untreated; 2) X-ray radiation; 3) X-ray radiation plus bone marrow transplantation with donor bone marrow cells from transgenic mice expressing enhanced green fluorescent protein (GFP) on a universal promoter. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…1b), which strongly suggests that the DP recovery is achieved by self-proliferation rather than by the influx from the DN population. However, evidence about the self-proliferation ability and speed of DP cells is inconsistent and may depend on strains 36,37 ; some studies showed that DP cells proliferate little 22,38 while others have suggested that DP cells can proliferate faster than other types of thymocytes 37,39 . Our model coordinates these properties with auto-inhibitory regulation of the DP proliferation, represented by the logistic term in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…1b), which strongly suggests that the DP recovery is achieved by self-proliferation rather than by the influx from the DN population. However, evidence about the self-proliferation ability and speed of DP cells is inconsistent and may depend on strains 36,37 ; some studies showed that DP cells proliferate little 22,38 while others have suggested that DP cells can proliferate faster than other types of thymocytes 37,39 . Our model coordinates these properties with auto-inhibitory regulation of the DP proliferation, represented by the logistic term in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + CD8 + cells, which comprise 75% of the T cells, transfer to the thymic cortex where they mature under the control of histocompatibility antigen‐directed processes that promote either loss of CD8 to generate CD4 + cells (T helper cells) or loss of CD4 to provide CD8 + cells (cytotoxic T cells), in a ratio of approximately 5–1 (Li et al. ). Despite the extensive suppression of thymocytes by DMBA and BP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following secondary antibody incubation for 1 hour at room temperature, slides were finally covered with Vectashield (Vector Laboratories, Burlingame, CA) solution and read using fluorescence microscopy (Zeiss, Berlin, Germany). Immunohistochemical staining was employed for detecting BMI‐1 protein expression in spleen and lymph node as described . Mouse‐derived monoclonal anti‐BMI‐1 antibody (Minipore, Billerica, MA) was employed in this study.…”
Section: Methodsmentioning
confidence: 99%